Phenotypic variation in Heliconius erato crosses shows that iridescent structural colour is sex-linked and controlled by multiple genes. Issue 1 (14th December 2018) - Brien, Melanie N.; Enciso-Romero, Juan; Parnell, Andrew J.; Salazar, Patricio A.; Morochz, Carlos; Chalá, Darwin; Bainbridge, Hannah E.; Zinn, Thomas; Curran, Emma V.; Nadeau, Nicola J.
Abstract : Bright, highly reflective iridescent colours can be seen across nature and are produced by the scattering of light from nanostructures. Heliconius butterflies have been widely studied for their diversity and mimicry of wing colour patterns. Despite iridescence evolving multiple times in this genus, little is known about the genetic basis of the colour and the development of the structures which produce it. Heliconius erato can be found across Central and South America, but only races found in western Ecuador and Colombia have developed blue iridescent colour. Here, we use crosses between iridescent and non-iridescent races of H. erato to study phenotypic variation in the resulting F2 generation. Using measurements of blue colour from photographs, we find that iridescent structural colour is a quantitative trait controlled by multiple genes, with strong evidence for loci on the Z sex chromosome. Iridescence is not linked to the Mendelian colour pattern locus that also segregates in these crosses (controlled by the gene cortex ). Small-angle X-ray scattering data show that spacing between longitudinal ridges on the scales, which affects the intensity of the blue reflectance, also varies quantitatively in F2 crosses.